Dexamethasone Coanalgesic Administration in Steroid Naïve and Steroid Non-Naïve Patients for the Prevention of Pain Flares after Palliative Radiotherapy for Bone Metastases - Dimitar G. Tonev; Silvia A. Lalova; Elena P. Petkova-Lungova; Nikolay V. Timenov; Gabriela M. Radeva; Todor G. Kundurzhiev (Pain Research and Management)
Objective. Dexamethasone could be an effective prophylactic agent for the prevention of pain flares after palliative radiotherapy (RT) for uncomplicated bone metastases. To date, there are no data on its prophylactic coanalgesic (opioid-sparing) effect after RT in patients with complicated bone metastases compared to uncomplicated ones, which is the aim of our study. Methods. Twenty-nine American Society of Anaesthesiologists (ASA) III-IV patients, aged ≥18, treated with single-fraction 8 Gy/1 or multi-fraction 20 Gy/5 RT for painful uncomplicated bone metastases (steroid naïve patients, n = 14) or complicated ones (steroid non-naïve patients, n = 15), were examined retrospectively. All patients received parenteral dexamethasone (4 mg or 8 mg daily, 1 hour before RT, followed by the same dose for the next 4 days) along with their background and breakthrough pain opioid intake (morphine equivalents) during their 5-day in-hospital stay. Pain severity (numeric rating scale) and analgesic consumption were recorded at admission, daily during the hospital stay, and for 10 days following treatment. Binary logistic regression was used to determine predictive factors for pain flare occurrence. Results. A higher ASA score is the only determinant positively influencing opioid consumption (P = 0.018) and pain flare as well (OR = 15.00; 95% CI: 2, 24–100, 48; P = 0.005). Lower dose 4 mg dexamethasone was revealed as a moderate analgesic agent in steroid naïve patients with no side effects, whereas in steroid non-naïve patients the predominantly higher dose 8 mg dexamethasone had minimal impact on pain flares prevention at the expense of more pronounced immunosuppression (P = 0.039). Conclusions. Irrespective of the supporting evidence of dexamethasone potential for prevention of RT-induced pain flare, our data failed to reveal its efficacy in the real practice world (a case mix of uncomplicated and complicated bone metastases). Further dose-effect bigger studies are needed, identifying optimal doses of dexamethasone intake and its optimal duration in high-risk patients.